The Early Divisome Protein FtsA Interacts Directly through Its 1c Subdomain with the Cytoplasmic Domain of the Late Divisome Protein FtsN - Busiek, Kimberly K. (American Society for Microbiology, 2012)
In Escherichia coli, FtsN localizes late to the cell division machinery, only after a number of additional essential proteins are recruited to the early FtsZ-FtsA-ZipA complex. FtsN has a short, positively charged cytoplasmic domain (FtsN(Cyto)), a single transmembrane domain (FtsN(TM)), and a periplasmic domain that is essential for FtsN function. Here we show that FtsA and FtsN interact directly in vitro. FtsN(Cyto) is sufficient to bind to FtsA, but only when it is tethered to FtsN(TM) or to a leucine zipper. Mutation of a conserved patch of positive charges in FtsN(Cyto) to negative charges abolishes the interaction with FtsA. We also show that subdomain 1c of FtsA is sufficient to mediate this interaction with FtsN. Finally, although FtsN(Cyto-TM) is not essential for FtsN function, its overproduction causes a modest dominant-negative effect on cell division. These results suggest that basic residues within a dimerized FtsN(Cyto) protein interact directly with residues in subdomain 1c of FtsA. Since FtsA binds directly to FtsZ and FtsN interacts with enzymes involved in septum synthesis and splitting, this interaction between early and late divisome proteins may be one of several feedback controls for Z ring constriction.